Are Elasticities of Taxable Income Rising? - Klemm, Alexander (IMF Working Papers; Working Paper ;, 2018)
This paper assesses a possible explanation for the global downward trend in top personal income tax rates over the last decades: globalization and the related tax evasion and avoidance opportunities could have raised elasticities of taxable income, which would imply lower optimal tax rates. The paper estimates elasticities of taxable income for top income earners using a large sample of economies and years with a common method, allowing an analysis of trends in such elasticities. The paper finds that elasticities do not appear to exhibit any clear pattern over the years. The downward trend in tax rates must have other possible explanations, which are briefly discussed.